PENGGUNAAN KOMPUTASIONAL LINGUISTIK DALAM ETIKA PROFESI BERKEBANGSAAN - Purwadi; Dewi, Mutiara Indah Nirmala (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
The development of information technology has brought significant changes to the dynamics of this nation’s life. Its utilization can transform societal habits, as it not only increases efficiency within work frameworks but also demands the application of professional ethics through more advanced computational linguistics in a digital society. This research aims to analyze the role of information technology in supporting the implementation of professional ethics and to identify the challenges and opportunities arising from the integration of technology in professional practices using computational linguistics. The methods used include literature studies, document analysis, and case reviews related to professional ethics in the digital era. The findings show that information technology contributes to strengthening ethical values such as transparency, accountability, and information openness. However, technology also presents risks, including privacy violations, data misuse, and decreased professional integrity if not accompanied by adequate supervision and digital literacy. These findings affirm that the implementation of professional ethics must progress in tandem with technological development through clear regulations, increased ethical awareness, and secure digital infrastructure support. Overall, this study emphasizes the importance of synergy between information technology and professional ethics to create a work environment that upholds integrity and earns public trust.